Modifying elastic modulus of two-component polyurethane adhesive for structural hardwood bonding - Bockel, S.; Harling, S.; Konnerth, J.; Niemz, P.; Weiland, G.; Hogger, E.; Pichelin, F. (Journal of wood science, 2020)
Subject to this study is the modification of an experimental two-component polyurethane (2C PUR) as an alternative adhesive for structural hardwood bonding. The 2C PUR has been adapted by calcium carbonate as filler to increase its modulus of elasticity with the aim of increasing the modulus analogue to the ones typically observed for classic amino- and phenol based adhesives. The 2C PUR system was compared with a commercial one-component polyurethane (1C PUR) and a phenol resorcinol formaldehyde (PRF) adhesive. The wetting properties of the adhesives were tested in terms of surface tension, polar and dispersive part and contact angle on European beech wood ( Fagus sylvatica L.). In addition, adhesive polymer films of 2C PUR were tested for tensile strength and modulus of elasticity (E-Modulus) following ISO 527-1. The adhesives bond performance on beech wood was determined by lap-joints according to EN 302-1 in various climate conditions. The results show that 2C PUR has proper wettability properties on beech wood. Adding 60% wt filler to the polyol component increased the E-Modulus from 2.3 GPa (0%) to 4.4 GPa. The tensile strength of the modified 2C PUR polymer films was comparable with the industrial 1C PUR. Tensile shear strength and wood failure percentage of 2C PUR lap-joints were increased by adding filler and met requirements in dry and re-dried conditions according to EN 302-1. However, the addition of filler didn’t result in an improvement in wet conditions. The present study shows sufficient performance for bonding hardwood with 2C PUR in dry conditions, while the system still needs to be improvement regarding its performance in humid conditions.